Coupling of transients in HVDC lines to adjacent HVAC lines and its impact on the AC line protection - Arro, Tõnn; Silavwe, Owen (My University, 2007)
With stringent environmental regulations in the world today, acquisition of new rights-of-way (RoW) for transmission projects by electricity companies is at a premium. Faced with this scenario, electricity utilities naturally opt to optimise existing RoW with the consequence that distances between transmission lines in the same RoW are being pushed to the limits. The concern however, for transmission lines located in close proximity with each other is that at non-dc frequency, they will influence each other through electromagnetic coupling. Of interest also is the effect, if any at all, of the resulting coupling on the protection system of the coupled circuit. Svenska Kraftnät (SvK), the Swedish National Grid company, is currently working to expand the existing monopolar 400kV, 600MW Fenno-Skan HVDC link between Sweden and Finland into a bipolar ±500kV, 1400MW link. As one consequence of this expansion, two sections of mutually coupled overhead lines will be created; one coupled section of about 53km will be formed between the second pole (new pole) of the ±500kV HVDC link and an existing 400kV HVAC line and another coupled section between the same pole of the HVDC link with an existing 220kV HVAC line of about 7.5km. The coupled sections arise since the first 70km of the second pole of the HVDC link will be constructed as an overhead line mainly within existing RoWs before transforming into an undersea cable en-route to Finland. In this thesis, the coupling of transients to the HVAC lines that could arise due to a pole-toground fault occurring on the HVDC line has been studied in respect of the above mentioned coupled line sections. Furthermore, assessement of the impact of the coupling phenomenon on the ground protection of the HVAC lines has been carried out. The study has been carried out using models developed in PSCAD/EMTDC and MATLAB. The PSCAD/EMTDC model is detailed, taking the form of a full system representation. The MATLAB model is more of a conceptual model, based on solving a system of coupled transmission line travelling wave equations. Good agreement between results from the two models has been achieved. The conclusions of the study are that the coupling phenomenon is mainly due to coupling in zero seuqence networks. Peak values for the RMS coupled zero-sequence currents of 1200A and 700A for total and fundamental currents respectively can be expected. These currents are transient in nature and they decay to zero within about 60-80ms. The study further concludes that the ground overcurrent protection of the coupled 400kV and 220kV AC transmission lines in the SvK system will not be called into operation as a result of the coupled current flowing in them. Finally the study concludes that the ground protection settings in the SvK system can be said to be adequately and properly set such that no unwanted tripping will occur due to this type of coupling phenomenon.
Keywords: Elkraftteknik; Electric power engineering